Shared temporal cognitions as substitute for temporal leadership: an analysis of their effects on temporal conflict and team performance - Santos, C. M.; Passos, A. M.; Uitdewilligen, S.; Nübold, A. (Leadership Quarterly, 2016)
Due to changing organizational demands, team leaders increasingly need to engage in temporal leadership behaviors in order to coordinate team members’ efforts, avoid time related conflicts and ensure that teams perform well. Simultaneously, temporal conflicts and team performance are impacted by team members’ shared temporal cognitions. In this study, we investigate the effect of temporal leadership and shared temporal cognitions on team performance via temporal conflict and test whether the impact of temporal leadership on temporal conflict may be substituted by shared temporal cognitions. Our study was conducted in a management simulation involving 142 teams working on a task over 5 weeks. Results suggest that temporal conflict mediates the relationship between temporal leadership and team performance as well as between shared temporal cognitions and team performance. Further, we found support for the idea that shared temporal cognitions function as a substitute of temporal leadership for reducing temporal conflict in teams.